“Catholic” Ecclesial Groups in the Catholic Church and Polish Law - Świto, Lucjan; Tomkiewicz, Małgorzata (Studia Warmińskie, 2018)
The Congregation for the Doctrine of the Faith in the letter Iuvenescit Ecclesia, addressed to the Catholic bishops in June 2016, pointed out that there are doubts as to whether certain associations, which have the term "Catholic" in their name, actually have the right to use this word. The congregation also recalled that the essential element of Catholic associations should be the goal of acting responsibly to participate in the mission of the Church. In the above-mentioned article, and also on the basis of the analysis of normative regulations in force in the internal law of the Catholic Church and in Polish law, the principles of using in the names of institutions, associations, clubs, etc. the adjective "Catholic" are shown.